Lawsuit Suspension in the Sharia Procedure Code - Al Tawalbeh, Mansour Abdullah Fayyad (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to clarify the issue of lawsuit suspension in the Jordanian Shari’a Procedure Code. The study explores the types of lawsuit suspension, its impact on pending cases, and the conditions under which this suspension expires and its duration. Methods: The research employs an inductive approach to explain the concept of lawsuit suspension and follows the provisions outlined in the Shari’a Procedure Code pertaining to this subject. The study examines procedural images through the analysis of legal provisions. The researcher also utilizes the analytical approach to dissect legal texts and links them to the issue of suspension and how it’s terminated. Additionally, a descriptive approach is adopted to identify the procedural images through the study of legal provisions. Results: The research concludes that the Jordanian Shari’a Procedure Code, while addressing the issue of lawsuit suspension, does so in a fragmented manner, lacking comprehensive coverage on how to implement the legal texts concerning the termination and duration of the stay of the lawsuit Conclusion: Lawsuits’ suspension in the Shari’a Procedure Code is a critical judicial manner with significant implications. Therefore, it is imperative to address the necessity of reviewing the legislation governing this subject.